Early versus late nephrology referral and patient outcomes in chronic kidney disease: an updated systematic review and meta-analysis - Linan Cheng; Nan Hu; Di Song; Li Liu; Yuqing Chen (BMC Nephrology)
Abstract Background Nephrology referral has been recognized as a modifiable factor influencing patient outcomes. The study aimed to compare clinical outcomes among patients referred early versus late to nephrologists. Methods We searched online database from inception to June 1, 2022, to obtain all eligible literature reporting outcomes of patients referred early versus late to nephrologists. The early and late referral was defined by the time at which patients were referred to nephrologists before dialysis onset. Results Seventy-two studies with over 630,000 patients met the inclusion criteria. A lower likelihood of all-cause mortality (HR = 0.67, 95% CI: 0.62–0.72) was achieved among patients referred early to nephrologists. The survival advantage of early referral was apparent in the first 6 months and extended to the 5th year after dialysis onset (6 months: HR = 0.52, 95% CI: 0.40–0.68; 5 years: HR = 0.67, 95% CI: 0.60–0.74). The early referral was associated with shorter durations of initial hospitalization, a higher rate of kidney transplantation (RR = 1.41, 95% CI: 1.12–1.78), a lower likelihood of emergency start (RR = 0.39, 95% CI: 0.28–0.54), a higher likelihood of permanent access creation (RR = 3.34, 95% CI: 2.43–4.59), increased initial use of permanent access (RR = 2.60, 95% CI: 2.18–3.11), and reduced initial catheter use (RR = 0.43, 95% CI: 0.32–0.58). Conclusions Our study showed a lower risk of mortality, shorter lengths of initial hospitalization, and better preparations for renal replacement therapy among patients referred early to nephrologists. Early nephrology care should be promoted to improve the management of advanced chronic kidney disease.